The 'team of 5 million': The joint construction of leadership discourse during the Covid-19 pandemic in New Zealand. (October 2021) - Hafner, Christoph A.; Sun, Tongle
Abstract: The Covid-19 pandemic that swept the world in 2020 demanded action from political leaders around the world to lead their people through the crisis. Leadership in a crisis involves a range of activities, such as making responsive decisions, communicating those decisions to the public, envisioning goals, generating trust and cooperation, and appealing for collective actions. Effective communication plays an essential role in this process. New Zealand has been regarded as a successful case globally in its crisis response to the Covid-19 pandemic. This study investigates the role of language and discourse in New Zealand's Covid-19 crisis leadership and communication practices. Informed by an interactional sociolinguistics approach, the study draws on frame analysis, positioning theory, and rhetorical analysis to examine how the Prime Minister, Jacinda Ardern, her leadership team, and New Zealand mainstream media jointly negotiated and co-constructed the leadership discourse. Drawing on a corpus of 98 New Zealand government press briefings, a selected subset of press briefings surrounding significant events at the beginning of the first wave (March 2020) and second wave (August 2020) were coded and analyzed. The study identified a range of discursive strategies employed by Ardern at press briefing speeches and the question and answer sessions. Multiple self-positionings of Ardern and interactive positionings of the virus, the New Zealand government, and New Zealanders were identified. Ardern's metaphorical framings of the crisis as a 'fight' and the response as a collective action provided the basis for rhetorical appeals to the public in the management of the pandemic. A close examination of the ways Ardern responded to media resistance of her discursive framing demonstrated that New Zealand leadership during the pandemic was not only discursively constructed, but also jointly and collaboratively achieved by multiple actors.